A scoping review on innovative methods for personality observation - Mosca, Lucia Luciana; Continisio, Grazia Isabella; De Lucia, Natascia; Gigante, Elena; Guerriera, Carmela; Maldonato, Nelson Mauro; Moretto, Enrico; Ragozzino, Ottavio; Rosa, Veronica; Scognamiglio, Chiara; Stanzione, Roberta; Cantone, Daniela (Frontiers in Psychology, 2023)
Background Personality’s investigation has always been characterized as a central area of research for psychology, such that it was established in the 1920s as an autonomous scientific-disciplinary field. Identifying and observing the people’s typical ways of “being in the world” has made possible to define the predictability of a pattern of behavioral responses related both to the possession of distinct characteristics of the agent subject and to specific environmental situations. In the actual scientific landscape, there is a strand of research that makes a description of personality through methodologies and indicators not usually used by psychology, but scientifically validated through standardized procedures. Such studies seem to be significantly increasing and reflect the emerging need to have to consider the human being in his or her complexity, whose existential and personal dimensions can no longer be traced to classification systems that are divorced from the epochal reference. Objective In this review, attention is focused on highlighting publications in the literature that have included the use of unconventional methods in the study of nonpathological personality, based on the Big Five theoretical reference model. To better understand human nature, an alternative based on evolutionary and interpersonal theory is presented. Design Online databases were used to identify papers published 2011–2022, from which we selected 18 publications from different resources, selected according to criteria established in advance and described in the text. A flow chart and a summary table of the articles consulted have been created. Results The selected studies were grouped according to the particular method of investigation or description of personality used. Four broad thematic categories were identified: bodily and behavioral element; semantic analysis of the self-descriptions provided; integrated-type theoretical background; and use of machine learning methods. All articles refer to trait theory as the prevailing epistemological background. Conclusion This review is presented as an initial attempt to survey the production in the literature with respect to the topic and its main purpose was to highlight how the use of observational models based on aspects previously considered as scientifically uninformative (body, linguistic expression, environment) with respect to personality analysis proves to be a valuable resource for drawing up more complete personality profiles that are able to capture more of the complexity of the person. What has emerged is a rapidly expanding field of study.